Poetic Manifestos and Democracy (in Poland after 1989) - Hoffmann, Krzysztof (Poznańskie Studia Slawistyczne, 2019)
A form of poetic manifesto rooted in the avant-garde tradition is construed here as a performative project of the future. This temporal quality links it with the Derridean notion of “democracy to-come”. The presented paper attempts to trace an (im)possible connection between poetic manifestos and democracy in Poland after 1989. In pursuance of this objective, the paper briefly presents the only four 21st‑century Polish manifestos that attracted some critical and/or artistic attention: Meblowanie główww, Manifest Neolingwistyczny v. 1.1, Manifest poezji cybernetycznej and Manifest Rozdzielczości Chleba v. 1.7.